Analisis Kebutuhan Pengembangan Aplikasi Mobile Learning untuk Pembelajaran Matematika di Sekolah Menengah Pertama - Laswadi Laswadi (Journal on Education, 2022)
In facing current educational challenges, mobile learning can be an alternative solution to facilitate the teaching and learning process. It is mobile because mobile learning can be accessed via devices such as smartphones and tablets, which are almost always in the hands of students and teachers. However, to achieve effectiveness in developing mobile learning, needs analysis is essential. By conducting a needs analysis, we can understand the characteristics of the learner, learning materials, as well as the learning environment and conditions. The purpose of this article is to analyze the needs for developing mobile learning applications for learning mathematics for junior high school students on the topic of area and perimeter of quadrilaterals. This research is a descriptive exploratory study. The research subjects were seventh grade students at SMPN 4 Kerinci. A random sample of 15 students was selected. Data were collected using observation sheets of the mathematics learning process and student questionnaires. The observation results show that the mathematics learning material is still in the form of textbooks. The results of the needs analysis questionnaire show that students need learning media that can guide them to study independently by reviewing lessons anytime and anywhere in the form of mobile learning.